2009
DOI: 10.1007/s10725-009-9382-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation in response to heavy metals during vegetative growth in Dorycnium pentaphyllum Scop.

Abstract: Seeds, young plants and adult plants of the perennial Mediterranean leguminous shrub Dorycnium pentaphyllum Scop. were exposed to Cd (1-100 lM) or Zn (10-10,000 lM) on nutrient solution. This species is resistant to Cd and Zn at different phenological stages. The lowest doses of Zn and Cd improved seed germination and young seedling growth, while only the highest doses of both heavy metals inhibited germination and decreased growth. High doses of Cd reduced seed imbibition and young seedling water content, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…The addition of the lowest Zn concentrations (100 and 1,000 μM) had no significant impact on the seed germination of Dorycnium pentaphyllum Scop, which has been nominated as a Zn-tolerant plant (Lefèvre et al 2009). The results of the present study also suggested that the zinc concentration range of 10 to 400 μM did not significantly affect seed germination as compared to that of the control; thus Moso bamboo seeds have strong tolerance to Zn stress.…”
Section: Discussionmentioning
confidence: 98%
“…The addition of the lowest Zn concentrations (100 and 1,000 μM) had no significant impact on the seed germination of Dorycnium pentaphyllum Scop, which has been nominated as a Zn-tolerant plant (Lefèvre et al 2009). The results of the present study also suggested that the zinc concentration range of 10 to 400 μM did not significantly affect seed germination as compared to that of the control; thus Moso bamboo seeds have strong tolerance to Zn stress.…”
Section: Discussionmentioning
confidence: 98%
“…Unregulated ROS molecules can chemically react with nucleic acids and affect the genetic code of the embryo and react with seed storage compounds such as proteins and lipids, thus compromising the germination process (Kranner & Colville 2011). Slightly enhanced levels of oxidative stress have been observed to stimulate germination (Lefevre et al 2009), however, as germination processes are strictly regulated by ROS concentrations .…”
Section: Ros the Environment And Seed Germinationmentioning
confidence: 99%
“…organic acids, phytochelatins (PCs) or metallothioneins) (Cobbett and Goldsbrough 2002). However, the responses of plants in terms of not only growth but also accumulation and distribution of toxic metal ions may be influenced by ontogeny (Krupa and Moniak 1998;Skorzynska-Polit andBaszyński 1995, 1997;SkorzynaskaPolit et al 1995;Dra̧zkiewicz et al 2003;Lefèvre et al 2009;Dobroviczká et al 2013). It has been shown that metal distribution in maize and rye plants depends on their age as well as metal concentration in the growth medium (Dra̧zkiewicz et al 2003;Krupa and Moniak 1998).…”
Section: Introductionmentioning
confidence: 99%